Immersive Digital Technology and Media - Nevil Pradeep Dsouza, Dr. Bhargavi Hemmige, (International Journal of Advanced Science and Technology, 2020)
We live in an innovation soaked world relying upon a variety of traditional and new media for information, entertainment, and connection. As we traveled through the ages, mass communication developed from a mechanical component to electronic conveyance, preparing for the present digitized world. While technological advancements are an integral part of the media narrative. This study throws some insights on the immersive technology such as Augmented Reality (AR), Virtual Reality (VR), Mixed Reality (MR) and 360 Degree Video that is used in media and its interventions in the media market. Also, this study refers to the uses and Gratification theory to analyse how media is upgrading to get audience attention and impact of technology in media.